CT manifestations and differentiation of thymic squamous cell carcinoma - LU Li-jun; GUO Jian-wei; ZHANG Ming (Zhongguo linchuang yanjiu, 2022)
Objective To explore the CT imaging features and differentiation of thymic squamous cell carcinoma to improve the recognition and diagnosis level of it. Methods Of 39 patients with thymic tumor confirmed by surgery or puncture pathology from June 2014 to June 2021 in Sengong Hospital of Shannxi Province, 25 patients with thymic squamous cell carcinoma were collected as observation group and 14 patients with high-risk thymoma were served as control group. The clinical manifestations, Masaoka staging and CT signs were summarized and compared between two groups. Results The Masaoka staging system showed that most of thymic squamous cell carcinoma were stage Ⅲ(28.0%, 7/25) and stage Ⅳ(52.0%, 13/25) in observation group, which were significantly different from those in control group( χ2=9.762, P=0.021). The incidences of lobulated tumor, blurred boundaries, pericardial invasion, mediastinal fat infiltration in observation group were statistical higher than those in control group(P＜0.05). There was no significant difference in tumor internal partition, density, degree of enhancement, calcification and cystic, perfusion type growth, invasion of large vessels, pleural invasion, lymph node metastasis, pulmonary metastasis and pleural implantation between two groups(P＞0.05). Conclusion There is no obvious specificity in the clinical manifestations of thymic squamous cell carcinoma. CT manifestations are mostly characterized by anterior middle and upper mediastinal lobular mass with blurred boundaries and perfusion growth along macrovascular shape in some of them. The tumor is highly invasive to surrounding tissues and can invade macrovascular, pleura and pericardium. Mediastinal fat infiltration are common, and Masaoka staging is mostly stage Ⅲ and Ⅳ.